EFEKTIVITAS PEMBEBASAN/PENGHAPUSAN SANKSI ADMINISTRASI PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR DI PROVINSI RIAU - Dikky Maihendra; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research is based on the phenomenon where there are many vehicle tax arrears so that the government provides relief to the community through the exemption / elimination of motor vehicle tax administration sanctions and motor vehicle name transfer fees in Riau province. This type of research uses a descriptive research method with a qualitative approach. The focus of this research is based on the study of program effectiveness theory according to Mahmudi in Fransiska (2015: 86), in this case there are 4 studies, namely, Input; the implementation here is preparatory, starting from regulation, coordination, resources, and in implementing the input it is good. Process; of the program is effective because in the implementation process it can be said that it is good. Output; from the motor vehicle tax sanction exemption program is to increase Regional Original Income, and after the program is running, it can be seen that the Regional Original Income has increased, indicating the program has been effective. Outcome; of this program is to make people who comply with taxes, and this has received a positive response from the community because most people who are overdue on taxes pay their obligations. The implementation of the motor vehicle tax sanction exemption program in Riau province is appropriate because it is seen from the right target, implementation time, and the purpose of the tax sanction exemption policy being created. Keywords: Effectiveness, Tax, Sanction Waiver Program